Prioritizing information over grammar: a behavioral investigation of information density and rhetorical discourse effects on EFL listening comprehension - Mohamed A. Mekheimer; A. I. Fageeh (Discover Education)
Abstract This study investigated the impact of information density on English as a Foreign Language (EFL) listening comprehension, testing the hypothesis that listeners prioritize message understanding in information-rich discourse over grammar-focused analysis in rhetorical discourse. A quasi-experimental design was employed with 26 EFL college students, who listened to two audio passages: one information-rich and the other rhetorical. Behavioral measures, including listening comprehension scores and response times, revealed that participants demonstrated significantly higher comprehension accuracy (96% vs 44.3% accuracy) and faster processing times (37 min versus 41 min) when listening to the information-rich audio compared to the rhetorical audio (p < .005). Survey data further indicated that participants prioritized semantic content extraction over grammatical analysis, especially when engaging with the rhetorical passage. These findings support the hypothesis that listeners strategically adjust cognitive processing based on discourse information density, favoring meaning extraction in more informative contexts, with a decrease in grammatical parsing routines. The results highlight the role of information density in L2 listening comprehension and suggest that language learning materials should prioritize informative discourse to facilitate more efficient and effective processing.